CAPACITY BUILDING OF THE INSPECTORATE IN CONDUCTING INVESTIGATIVE AUDITS IN ROKAN HILIR REGENCY - Khairul Rahman; Ramadan; Annisa (International Conference On Law And Social Sciences, 2024)
The Inspectorate of Rokan Hilir Regency, as a Government Internal Supervisory Apparatus (APIP), plays a central role in ensuring accountability and effectiveness in financial and operational management at the regional level. To fulfill this role, the Inspectorate of Rokan Hilir Regency must continuously built its capacity to align with its functions. This research aims to analyze and evaluate the efforts of capacity building of the Inspectorate of Rokan Hilir Regency in conducting investigative audits. This study analyzes the strengths and weaknesses as well as the factors hindering the capacity building of the Inspectorate of Rokan Hilir Regency from the aspects of human resources development, organizational strengthening, and institutional reform. The research method employed in this study is qualitative research method, with direct interviews conducted with key informants such as Inspectors, Auditors at the Inspectorate of Rokan Hilir Regency, and auditees who have undergone investigative audits. The conclusion drawn by the researcher during the research implementation is that the Capacity Building of the Inspectorate in conducting Investigative Audits in Rokan Hilir Regency has not been optimally executed. This conclusion is based on the analysis of 3 (three) indicators, namely: Human Resources Development, Organizational Strengthening, and Institutional Reform. Among these indicators, the Human Resources Development indicator with assessment items of Recruitment and Training, and Education (training) of investigative audits are still low in implementation. Consequently, there are some auditors who still have antipathy towards the implementation of investigative audits. The research found several factors hindering the Capacity Building of the Inspectorate in conducting Investigative Audits in Rokan Hilir Regency, including budgetary constraints, auditor recruitment, the limited number of auditors participating in investigative training, and the absence of investigative audit guidelines.